An analysis of service delivery satisfaction levels for local authorities in Zimbabwe: the case of Victoria Falls Municipality (2010- 2015) - Imedi, Nothando (Midlands State University, 2017)
Public service delivery is of paramount importance to citizens around the globe. Service delivery is therefore meant to ensure good living conditions to the people thus there is need for good public service delivery. It can be noted that there are many factors that have been alluded to as causes of poor service delivery by local authorities and these factors are financial constraints, economic instability, political interference into the local authority issues and management thereby leading to poor public service delivery by local authorities in Zimbabwe. Therefore the aim of this study is to analyse the service delivery satisfaction levels for local authorities in Zimbabwe a case of Victoria Falls Municipality. To come up with a sound thesis three specific objectives with their underling hypothesis were designed and assessed by quantitative& qualitative research design. Following the fact that the research was a case study approach the researcher greatly employed primary and secondary sources of data, thus made use of online Articles, books, journals, interviews, questionnaires and even observations in order to produce a sound thesis. Background information on the proposed hypothesis the theoretical framework was established, conceptual and related literatures were also reviewed. After conducting the study, the researcher found out that there was need for improvement in service delivery by local authorities noting that a sound relationship between the service providers and the service users was to be establishes so as to allow effective communication that will enable efficient and effective service delivery.